2016
DOI: 10.1002/1873-3468.12091
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide‐dependent conformational changes of the AAA+ ATPase p97 revisited

Abstract: Edited by Peter BrzezinskiThe ubiquitous AAA-ATPase p97 segregates ubiquitylated proteins from their molecular environment. Previous studies of the nucleotide-dependent conformational changes of p97 were inconclusive. Here, we determined its structure in the presence of ADP, AMP-PNP, or ATP-cS at 6.1-7.4 A resolution using single particle cryo-electron microscopy. Both AAA domains, D1 and D2, assemble into essentially six-fold symmetrical rings. The pore of the D1-ring remains essentially closed under all nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 37 publications
0
62
0
Order By: Relevance
“…S1 and S2). The map shows VAT in a split-ring conformation that has not been observed previously for p97/VCP (38)(39)(40)(41)(42). For the ATPγS-loaded state, 514 micrographs were collected and subjected to a similar analysis.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…S1 and S2). The map shows VAT in a split-ring conformation that has not been observed previously for p97/VCP (38)(39)(40)(41)(42). For the ATPγS-loaded state, 514 micrographs were collected and subjected to a similar analysis.…”
Section: Resultsmentioning
confidence: 62%
“…The sixfold symmetrical, stacked-ring conformation of ATPγS-loaded VAT resembles the crystal structure of homologous Mus musculus p97/VCP in complex with a mixture of ADP and ADPAlF 6 (42) and recent high-resolution cryo-EM structures of p97 in different nucleotide states (38,39) and in the presence or absence of an allosteric inhibitor (38). Consequently, it was surprising to observe that in the ADP-bound conformation, the protomers arrange in a helical manner so as to generate an asymmetrical, split-ring structure.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Other models postulate that the polypeptide chain inserts only shallowly into the D1 ring (for review, see Xia et al, 2016). Finally, it has been suggested that the large, nucleotide-dependent conformational changes of the N domains are sufficient to move a polypeptide chain (Schuller et al, 2016). In each of these cases, it is unclear how a continuous pulling force could be generated, although such a force would likely be required to extract a subunit from a tight multimeric complex or a multi-spanning protein from the ER membrane.…”
Section: Introductionmentioning
confidence: 99%